Does managerial ownership moderate the effect of firm value and corporate social responsibility disclosure on tax avoidance? Evidence from Indonesian Food and Beverage Companies - Michael Stefanus Marentek; Sonny Pangerapan; Priscillia Weku (The Contrarian : Finance, Accounting, and Business Research, 2026)
Taxes are one of the most important sources of state revenue for national development. However, companies often engage in tax avoidance to minimize tax expenses legally by taking advantage of loopholes in tax regulations. This study aims to analyze the effect of firm value and Corporate Social Responsibility (CSR) Disclosure on tax avoidance, with managerial ownership as a moderating variable, in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the period 2021–2024. This study uses a quantitative method with multiple linear regression analysis and Moderated Regression Analysis (MRA). The sampling technique used purposive sampling, resulting in 16 companies with a total of 64 firm-year observations. The data used are secondary data obtained from companies’ financial statements. The results show that firm value, CSR Disclosure, and managerial ownership do not have a significant effect on tax avoidance (t-test significance values of 0.366, 0.681, and 0.700, respectively; all p > 0.05). Managerial ownership is also unable to moderate the relationship between firm value and CSR Disclosure on tax avoidance (interaction-term significance values of 0.265 and 0.589, respectively). The simultaneous test results indicate that all research variables together do not significantly affect tax avoidance (F = 0.384, p = 0.765; R² = 0.019, Adjusted R² = − 0.030), indicating that the model explains only a small proportion of the variance in tax avoidance and that other factors outside the model are likely more influential.